Understanding Obesity: History, Epidemiology, Causes, Consequences and Comprehensive Solutions - Salwa M. El Shebini; Maha I.A. Moaty; Nihad H. Ahmed (Liaquat National Journal of Primary Care)
The purpose of this study is to provide an overview of obesity disease including its definition, prevalence, causes, complications, and management. Obesity is a global epidemic that contributes significantly to chronic diseases worldwide. Obesity was recognized by Hippocrates as a medical condition capable of causing health problems. Obesity is classified into several types based on factors such as body mass index (BMI), body fat distribution, waist-to-height ratio, causes, and potential health risks. Adipose tissue produces adipokines and activates inflammatory signaling pathways, accelerating the onset and progression of obesity-related illnesses. Obesity is the result of a complex interaction between community and individual factors. These categories include physical activity, food consumption and production, personal psychology, and social psychology, additionally, obesity studies have highlighted the importance of genetic factors. Being overweight and obese can be avoided by increasing the intake of whole grains, polyphenolicrich legumes, nuts, vegetables, and fruits, selecting probiotic strains completely restriction the intakes of simple sugars and soluble starch and soda beverages; replacing saturated fats with unsaturated fats and increasing physical activity levels. Although lifestyle management is still the primary treatment for this condition, both medication and bariatric surgery result in greater and more sustained weight loss.